THE STOCHASTIC APPROACHES OF PROCESSES’ DESIGN IN VACUUM-PLASMA FORMATION OF NANOSTRUCTURED COATINGS - I. A. Ivanou; D. V. Valeysky; M. K. KasinskI (Литьë и металлургия)
The calculations of the spatial and energy parameters of a single-component metal plasma flow which is moved in a process gas environment using a numerical algorithm of test particle stochastic method are discussed. The results of the calculations are used for determining of the plasma flow density distribution on the product surface and for the energy loss in the ion flow within vacuum vessel. The compositions of the process gas and ion plasma flow are investigated. A theoretical model of the adsorption layer formation on the surface of the product with the reliance of the various simultaneous events on the condensation surface is offered.